Efficacy of dupilumab plus topical corticosteroids in children with atopic dermatitis: A meta‐analysis of randomized controlled trials - Li Wang; Si‐Ning Wang; Ruil‐Li Zhang (Immunity, Inflammation and Disease)
Abstract Introduction Children with atopic dermatitis (AD) bear a significant burden of illness that adversely affects their quality of life. Objective To determine the efficacy of dupilumab and topical corticosteroids for the treatment of pediatric AD. Methods A comprehensive literature search was conducted using three prominent databases: Web of Science, PubMed, and Embase. Using a fixed‐effects or random‐effects model, the standard mean difference or risk ratios with 95% confidence intervals were calculated, and the trial protocol was listed as CRD42023408546. Results A total of 3 studies were included, and 896 participants met the inclusion criteria. The combined estimate showed that dupilumab plus topical corticosteroids had numerically greater efficacy in terms of Eczema Area and Severity Index (EASI)‐50, EASI‐75, EASI‐90, and Investigator Global Assessment (IGA) score of 0 or 1. Children who received topical corticosteroids and dupilumab achieved significantly higher Children's Dermatological Life Quality Index scores compared to those who received placebo. The number of individuals who achieved IGA 0/1 increased with the use of dupilumab and topical corticosteroids. Conclusions Dupilumab and topical corticosteroids can be used to treat symptoms in children with AD. However, given the substantial variation in treatment outcomes among studies, the findings should be interpreted with caution.